2019
DOI: 10.21037/gs.2019.12.07
|View full text |Cite
|
Sign up to set email alerts
|

The role of microwave ablation in management of functioning pancreatic neuroendocrine tumors

Abstract: Background: Surgical resection is considered to be the only potentially curative option for patients with pancreatic neuroendocrine tumors (pNETs). High risk rates of perioperative complications make minimally invasive ablative techniques a novel perspective and alternative treatment option for pancreatic neuroendocrine tumors. This study aims to present the first experience of using a microwave ablation in management of pNETs.Methods: Sechenov University has an experience of treating more than 400 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“… 68 70 The pancreas is a thermo-sensitive organ, and ablation of normal pancreas tissue can lead to an inflammatory reaction causing oedema, cystic transformation and later fibrosis. 66 , 71 The first human pilot feasibility and safety study of EUS–guided RFA of the pancreatic lesion was published in 2015 using the Habib™ EUSRFA probe. 68 , 69 This was a prospective multi-centre study in which eight patients were enrolled: six with pancreatic cystic neoplasms (four mucinous cystic neoplasms, one intraductal papillary mucinous neoplasm, and one micro-cystic adenoma) and two with pNETs.…”
Section: Discussionmentioning
confidence: 99%
“… 68 70 The pancreas is a thermo-sensitive organ, and ablation of normal pancreas tissue can lead to an inflammatory reaction causing oedema, cystic transformation and later fibrosis. 66 , 71 The first human pilot feasibility and safety study of EUS–guided RFA of the pancreatic lesion was published in 2015 using the Habib™ EUSRFA probe. 68 , 69 This was a prospective multi-centre study in which eight patients were enrolled: six with pancreatic cystic neoplasms (four mucinous cystic neoplasms, one intraductal papillary mucinous neoplasm, and one micro-cystic adenoma) and two with pNETs.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported two rare cases of paragangliomas of the pancreas, which are typically hypervascular, with cystic changes mimicking pNETs (64). Furthermore, especially non-functioning pNETs that are bigger in size, may invade surrounding structures and present with biliary obstruction, as the classic presentation for pancreatic adenocarcinomas (65)(66)(67)(68).…”
Section: Metastasis and Mimicsmentioning
confidence: 99%
“…In addition, MWA lacks reliance on tissue impedance, is not limited by water vaporization and charring, 7 does not need an electrical circuit, and has a lower cost than RFA. 8 …”
Section: Introductionmentioning
confidence: 99%